Frequency and quality of antenatal care with low birth weight: analysis of Demographic and Health Survey indonesia 2017 - Masdah, Siti; Dasuki, Djaswadi; Wahab, Abdul (Universitas Gadjah Mada, 2022)
Purpose: Efforts to reduce low birth weight (LBW) cases can be made by regularly conducting antenatal care (ANC) during pregnancy. The aim is to improve the quality of ANCs and the quality of mothers, fetuses, and newborns associated with ANC. The World Health Organization (WHO) recommends reducing perinatal mortality and increasing the ability of care of pregnant women to make at least eight visits during pregnancy. This study aims to prove WHO's recommendation of at least 8 times the effect of ANC on LBW events in Indonesia. Methods: This study used a retrospective cohort and observational study design. The sample in this study were all women of childbearing age who were respondents to the 2017 IDHS. Data testing was performed using univariable, bivariable, and multivariable analysis. The analysis was performed by logistic regression. Results: ANC frequency was 8 times proven to reduce LBW risk; the lower the ANC contact, the greater the LBW risk. The incidence of LBW is lower in mothers who get quality ANC services. Exposure to cigarette smoke, the area of ​​residence in Sulawesi, NTT, and NTB, and the distance of pregnancy affect the incidence of LBW without changing the relationship of the ANC frequency with LBW. Conclusions: Mothers who regularly perform pregnancy checks at least 8 times by the standards become protection for LBW.